Land use in Ward One of the Stutterheim district - Kopke, Desmond (Rhodes University, Faculty of Science, Department of Geography, 1962)
The work began with the production by the author of a geological map of the area, since this essential task had not previously been undertaken. A detailed study of the settlement plan, containing both European and African smallholders, was then made. This proved a very fruitful field of study, because within the area the settlement plan is undergoing dramatic changes which are having an effect on the land use pattern within the area. This study was concerned mainly with the production of a detailed land use map and a quantitative analysis of the land use distributions revealed by this map. The classification used fer the categories on the land use map closely resembles one used in the land use map of 'The Border Region' produced by the Border Regional Survey (1957/8) which was in turn based on the World Land Use Map classification. Accompanying this text are seven maps produced by the author, three of the land settlement plan (1: 50,000), one each of the geology (1: 50,000) and rainfall (1:125,000) and two of the land use (l: 50,000 and 1: 125,000) in the area. The field sheets (1: 18,000) which show the land use of the area in great detail, are to be found in the library of the Geography Departmont, Rhodes University in atlas form.
Keywords: Land use -- South Africa -- Stutterheim; Rural development -- South Africa -- Eastern Cape; Stutterheim (South Africa) -- Geography; Stutterheim (South Africa) -- Social conditions; Stutterheim (South Africa) -- History